Optimizing the use of Digital Forensics and Information Technology in Proving Criminal Acts of Electronic Document Forgery in Indonesia - Edwin Setiawan; Hartiwiningsih Hartiwiningsih (International Journal of Law, Crime and Justice, 2025)
The rapid development of information technology has significantly changed cybercrime, especially electronic document forgery. This re-search examines the utilization of digital forensics and information technology in proving the crime of electronic document forgery in In-donesia through a normative legal research approach. The research uses a statutory approach and a conceptual approach to analyze the ef-fectiveness of digital forensic methods in uncovering electronic crimes based on certain evaluation criteria including technical feasibility, legal acceptability, and procedural compliance with Indonesian law. The findings show that digital forensics has an important role in in-vestigating electronic document forgery, but faces complex implementation challenges. Key barriers include limited human resources, with only 147 certified digital forensics experts in Indonesia according to verified 2023 data from the Indonesian Digital Forensics Association (AFDI), and legal regulations that have not fully accommodated the evolving digital technology landscape. The research identifies signifi-cant technical barriers, such as the complexity of forensic technology, the volatility of digital evidence, and the rapid advancement of cyber-crime techniques. Through an examination of recent case studies including the Tokopedia data breach of 2023 and the Jakarta Administra-tive Court electronic document forgery case of 2022, this research demonstrates the practical application of digital forensics in Indonesian courts. The research proposes a balanced approach that fulfills both evidentiary and human rights protection requirements in digital inves-tigations. Strategic recommendations include strengthening the capacity of forensic laboratories, harmonizing legal regulations, and im-proving the competence of human resources in technology and law. This research contributes to the conceptual framework of cyber law enforcement by offering a comprehensive perspective on the evidentiary challenges of e-crime in the digital age.